THE ENVIRONMENT: CHALLENGES AND THE PATH TOWARD SUSTAINABILITY - Rakhmonova Zebokhon; Qandiyorova Aziza (TADQIQOTLAR, 2026)
Abstract: This article presents a comprehensive exploration of the environment and the urgent necessity to protect it in the modern era. Recent research, literature, and global activities show an increasing understanding of the complex relationship between human civilization and natural systems. The work dives deep into the issues of environmental degradation, climate change, the role of education and public awareness, as well as practical pathways toward sustainable future development.